RETRACTED: A novel therapeutic strategy of combined camrelizumab and apatinib for the treatment of advanced hepatocellular carcinoma - Yang, Qing; Li, Gengyu; Wu, Xiaoqiu; Lin, Haiying; Wu, Wanrui; Xie, Xiangpang; Zhu, Yu; Cai, Wei; Shi, Changsheng; Zhuo, Shengye (Frontiers in Oncology, 2023)
Objective: To investigate the clinical effect of apatinib combined with camrelizumab in patients with advanced hepatocellular carcinoma (HCC). Methods: 85 patients with hepatocellular carcinoma (HCC) admitted to the interventional oncology department were randomly divided into two groups. Apatinib and camrelizumab were administered to 42 patients in group A, whereas sorafenib was administered to 41 patients in group B for three months. The clinical efficacy was evaluated in terms of objective response rate (ORR), and disease control rate (DCR). Certain tumor markers like alpha-fetoprotein (AFP), carbohydrate antigen 199 ( CA199), carcinoembryonic antigen (CEA), hypoxia-inducible factor (HIF-1), immune function T lymphocyte subsets (CD3+, CD4+, CD8+, CD4+/CD8+) were determined before and after treatment. The serum levels of vascular endothelial growth factor (VEGF), osteopontin (OPN), aspartate aminotransferase (AST), and epidermal growth factor 7 (Egflt)] were observed. The survival time between the two groups was compared, such as progression-free survival (PFS) and median survival (OS). Finally, the toxicity and side effects data were also obtained. Results: The ORR and DCR of group A were 69.05% and 88.10%, respectively, which were significantly higher (P<0.05) than group B (ORR=53.66% and DCR=70.73%). After treatment, the AFP, CA199, CEA, and HIF-1 levels of both groups decreased significantly (P<0.05), and the respective biomarker levels of group A were lower than those of group B (P<0.05). Following treatment, CD3+, CD4+, CD4+/CD8+ index in group A significantly increased (P <0.05) while CD8+ level was significantly decreased (P <0.05). Compared to group B, a significant increase was observed in group A’s CD3+, CD4+, and CD4+/CD8+ index. There were no significant changes in CD3+, CD4+, CD8+, CD4+/CD8+ indexes before and after treatment in group B (P>0.05). The serum level of VEGF, OPN, EGF-7 and AST indexes of group A&B were decreased significantly (P<0.05). Conclusion: In treating HCC, combining apatinib and camrelizumab can reduce tumor markers, enhance the immune system and curative effect, and prolong patient survival. The underline mechanism is related to the down-regulation of VEGF, OPN and HIF-1 indexes.